Hyperphagia, Mild Developmental Delay But Apparently No Structural Brain Anomalies in a Boy Without SOX3 Expression. Issue 5 (5th March 2013) - Helle, Johan Robert; Barøy, Tuva; Misceo, Doriana; Braaten, Øivind; Fannemel, Madeleine; Frengen, Eirik
Abstract The transcription factor SOX3 is widely expressed in early vertebrate brain development. In humans, duplication of SOX3 and polyalanine expansions at its C‐terminus may cause intellectual disability and hypopituitarism. Sox3 knock‐out mice show a variable phenotype including structural and functional anomalies affecting the branchial arches and midline cerebral structures such as the optic chiasm and the hypothalamo‐pituitary axis. SOX3 is claimed to be required in normal brain development and function in mice and humans, as well as in pituitary and craniofacial development. We report on an 8‐year‐old boy with a 2.1 Mb deletion in Xq27.1q27.2, which was found to be inherited from his healthy mother. To our knowledge, this is the smallest deletion including the entire SOX3 gene in a male reported to date. He is mildly intellectually disabled with language delay, dysarthria, behavior problems, minor facial anomalies, and hyperphagia. Hormone levels including growth, adrenocorticotropic and thyroid stimulating hormones are normal. Magnetic resonance imaging (MRI) at age 6 years showed no obvious brain anomalies. Genetic redundancy between the three members of the B1 subfamily of SOX proteins during early human brain development likely explains the apparently normal development of brain structures in our patient who is nullisomic for SOX3. © 2013 Wiley Periodicals, Inc.